CO2@C84: DFT Calculations of Structure and Energetics - Zdeněk Slanina; Filip Uhlík; Takeshi Akasaka; Xing Lu; Ludwik Adamowicz (Inorganics)
Encapsulations of carbon dioxide into <semantics>D2</semantics>(22)-<semantics>C84</semantics> and <semantics>D2d</semantics>(23)-<semantics>C84</semantics> fullerenes are evaluated. The encapsulation energy is computed with the DFT M06-2X/6-31+<semantics>G*</semantics> approach corrected for the basis set superposition error evaluated by the counterpoise method. The resulting encapsulation energy for <semantics>CO2</semantics>@<semantics>D2</semantics>(22)-<semantics>C84</semantics> and <semantics>CO2</semantics>@<semantics>D2d</semantics>(23)-<semantics>C84</semantics> amounts to substantial values of −14.5 and −13.9 kcal/mol, respectively. The energy gain is slightly larger than for CO@<semantics>C60</semantics>, already synthesized with a high-temperature and high-pressure treatment—so that a similar preparation of <semantics>CO2@C84</semantics> could be possible. The calculated rotational constants and IR vibrational spectra are presented for possible use in detection. The stability of <semantics>(CO2)2</semantics><semantics>@C84</semantics> is also briefly discussed.